2024
DOI: 10.1017/s1755773923000383
|View full text |Cite
|
Sign up to set email alerts
|

Affective polarization in Europe

Markus Wagner

Abstract: Affective polarization, a concept that originated in the USA, has increasingly been studied in Europe’s multi-party systems. This form of polarization refers to the extent to which party supporters dislike one another – or, more technically, to the difference between the positive feelings towards the supporters of one’s own political party and the negative feelings towards the supporters of other parties. Measuring this gap in Europe’s multi-party systems requires researchers to make various important decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 118 publications
(170 reference statements)
0
7
0
Order By: Relevance
“…In a next step, we applied the most widely used measurement approach for affective polarization, the feeling thermometer 8 , 40 , in which respondents are asked to rate their feelings about a specific subject on a temperature scale 9 , 40 . First, we dichotomized the variable on the position regarding COVID-19 vaccination and classified respondents who indicated a value from 0 to 4 as opponents of COVID-19 vaccination (anti-vaccination group) and those who indicated a value from 6 to 10 as supporters of COVID-19 vaccination (pro-vaccination group).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a next step, we applied the most widely used measurement approach for affective polarization, the feeling thermometer 8 , 40 , in which respondents are asked to rate their feelings about a specific subject on a temperature scale 9 , 40 . First, we dichotomized the variable on the position regarding COVID-19 vaccination and classified respondents who indicated a value from 0 to 4 as opponents of COVID-19 vaccination (anti-vaccination group) and those who indicated a value from 6 to 10 as supporters of COVID-19 vaccination (pro-vaccination group).…”
Section: Resultsmentioning
confidence: 99%
“…Second, we employ two common approaches to measuring affective polarization—thermometer scores and character trait ratings—between the pro-vaccination and the anti-vaccination group, thereby shedding additional light on the conflict around COVID-19 vaccination. Third, our study contributes to our understanding of the social and political consequences of the COVID-19 pandemic, because numerous studies have shown that affective polarization destabilizes social cohesion and undermines democratic norms 9 , 18 22 . What is more, understanding vaccine-related divides is crucial for the development of effective public health policies, as affective polarization hinders their implementation 22 , 23 , thus undermining efforts to control the spread of infectious diseases and to limit their consequences for the health of the citizenry 24 – 26 .…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Experimental work could strengthen the body of evidence regarding the effect of polarization on participation. More work is also needed in the area of measurement to better understand the properties of existing measures of polarization and develop new ones (Wagner 2024;cf. also Druckman & Levendusky, 2019;Torcal & Comellas, forthcoming).…”
Section: Discussionmentioning
confidence: 99%